2018
DOI: 10.3357/amhp.4951.2018
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Adaptability to Isolated, Confined, and Extreme Environments

Abstract: This review identifies individual factors linked to adaptability under ICE conditions. Further studies are needed to verify causal directions and determine the relative importance of these factors.Bartone PT, Krueger GP, Bartone JV. Individual differences in adaptability to isolated, confined, and extreme environments. Aerosp Med Hum Perform. 2018; 89(6):536-546.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…The capacity to adapt to ICE environments may require these and/or other attributes. A recent systematic review of studies addressing adaptability under ICE conditions confirmed the importance of intelligence, emotional stability, openness, mastery, and hardiness (Bartone et al, 2018). This study found that past experience, active coping style, and a moderate level of introversion also facilitated adaptability under extreme conditions.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The capacity to adapt to ICE environments may require these and/or other attributes. A recent systematic review of studies addressing adaptability under ICE conditions confirmed the importance of intelligence, emotional stability, openness, mastery, and hardiness (Bartone et al, 2018). This study found that past experience, active coping style, and a moderate level of introversion also facilitated adaptability under extreme conditions.…”
supporting
confidence: 66%
“…Following grounded theory procedures for qualitative analysis as recommended by Charmaz (2006;2012) and Castleberry & Nolen (2018), a thematic analysis was performed on the interviews in order to identify the unique and recurrent issues within each of the content areas. In the first stage of analysis, a coding scheme was developed that reflected factors from the scientific literature previously found to be related to human adaptability in extreme environments (Bartone, Adler, & Vaitkus, 1998;Bartone et al, 2018). In the case of stressors for example, these included isolation, danger, uncertainty, powerlessness, and boredom.…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews have focused on individual differences in personality and other factors related to positive team performance in ICE environments, with an emphasis on space applications. 2,13,22 Bell et al 4 examined team composition variables and made a distinction between surface level (overt characteristics such as age, profession) and deep level variables (underlying psychological characteristics including personality and values). Deep level variables were considered to have a stronger and more enduring influence on team performance over time, as individuals get to know each other better.…”
Section: Discussionmentioning
confidence: 99%
“…Deep level variables were considered to have a stronger and more enduring influence on team performance over time, as individuals get to know each other better. Bartone et al 2 concluded that (deep level) emotional stability and personality traits, including openness, facets of conscientiousness, introversion, self-control, hardiness, and low need for social support, are characteristics optimal for performing in ICE environments.…”
Section: Discussionmentioning
confidence: 99%
“…It was evidenced for cold/heat and hypoxia ( Launay et al, 2006 ; Lunt et al, 2010 ; Keramidas et al, 2015 ; Gibson et al, 2017 ) which modified their interaction but broad data in this field of research is still missing due to difficulties of the measure so that a general conclusion cannot be drawn to date. The same accounts for the acclimatization response of each individual that seems to be affected by distinct differences ( Bartone et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%